The Bali Process and Global Refugee Policy in the Asia–Pacific Region. (28th June 2014) - Kneebone, Susan
Abstract : This article examines the role of two regional actors in the Asia–Pacific region, namely the Bali Process and the Asia Pacific Refugee Rights Network (APRRN), a platform of civil society organizations, as two very different models of mechanisms and agenda-setting on Global Refugee Policy (GRP). The Bali Process has limited actors and a narrow discourse on refugees which reflects a hierarchical agenda-setting process or 'steering mode'. By contrast, the APRRN is a non-state network actor which works through non-hierarchical mechanisms as a transnational activist network (TAN) and has a normative agenda. This article demonstrates the tension within GRP which is being created within the region through these two intermediaries between the global North and the global South.